Comparison of the effects of pea protein and whey protein on the metabolic profile of soccer athletes: a randomized, double-blind, crossover trial - Loureiro, Luiz Lannes; Ferreira, Tathiany Jéssica; Cahuê, Fábio Luiz Candido; Bittencourt, Victor Zaban; Valente, Ana Paula; Pierucci, Anna Paola Trindade Rocha (Frontiers in Nutrition, 2023)
Introduction: Pea protein (PP) concentrate is a plant-based alternative to animal protein sources, such as whey protein (WP). In addition to its valuable amino acid composition, PP has a low environmental impact, making it a sustainable, nutritious, and viable alternative for enhanced sports performance, such as in soccer. PP Therefore, this study aimed to evaluate the effects of PP and WP supplementation on biochemical and metabolic parameters in soccer players. Methods: Twelve male under-20 soccer players were included in this double-blind, randomized crossover intervention study. For 10 consecutive days, each participant received either 0.5 g/kg of the PP or WP supplementation after training, starting 7 days before the test game, and continuing until 2 days after. After a 4-day washout period, the athletes switched groups and the intervention was restarted. Blood samples were collected before and after the game, as well as 24 h, 48 h, and 72 h intervals thereafter. Creatine kinase (CK), aspartate transaminase, alanine transaminase (ALT), lactate (LA), urea, creatinine, and uric acid were analyzed using commercial kits. Exploratory metabolic profiling of the serum samples was performed using nuclear magnetic resonance spectroscopy. Results: A comparison of biochemical markers showed that the PP group had lower CK in the postgame moment, 24 h, and 48 h. Lower LA in the post-game moment, and lower ALT in the postgame moment and at 24 h. Of the 48 metabolites analyzed, 22 showed significant differences between the time points, such as amino acids, ketone bodies, and glucose metabolism. Glutamate and lactate levels significantly increased between the pre-and post-game moments in the WP group. After the game, the WP group exhibited reduced levels of metabolites such as arginine and taurine, whereas no such change was observed in the PP group. There was no difference in metabolites 72 h after the game. Conclusions: Despite the slight advantage of the PP group in specific biochemical markers, these differences are not sufficient to justify the choice of a particular type of protein. However, the results highlight the viability of plant protein as a potential alternative to animal protein without compromising athletic performance or recovery.